Knowledge, attitude, and practice of patients with type 2 diabetes mellitus with regard to their disease: a cross-sectional study among Palestinians of the West Bank - Ramzi Shawahna; Saed Samaro; Zaid Ahmad (BMC, 2021)
Abstract Background In Palestine, type 2 diabetes mellitus (T2DM) is a rapidly growing health concern. This study evaluated knowledge, attitude, and practice of patients with T2DM with regard to their disease. The study also investigated association and correlation between knowledge, attitude, and practice with sociodemographic and clinical characteristics of the patients. Predictors of higher knowledge, positive attitude, and good practice were also identified. Methods This cross-sectional study was conducted in primary healthcare facilities frequently visited by patients with T2DM across the West Bank of Palestine in the period of October 2018 to January 2019. An interviewer administered questionnaire was used to determine knowledge, attitude and practice of patients with T2DM with regard to their disease. Results Out of 300 patients invited, 220 (73.3%) patients responded. In this study, the median age was 57.0 years (51.0, 65.0), the median time elapsed since diagnosis with T2DM was 7.0 years (4.0, 14.0), the median fasting blood glucose was 150.0 mg/dL (128.8, 180.0), the median postprandial glucose was 230.0 mg/dL (200.0, 270.0), the median HbA1c was 7.8% (7.0, 8.53), and the median BMI was 28.8 kg/m2 (25.5, 33.1). The median knowledge score was 6.0/13.0 (4.5/13.0, 7.5/13.0), the median attitude score was 3.0/4.0 (2.0/4.0, 4.0/4.0), and the median practice score was 3.0 (1.0/5.0, 4.0/5.0). Having university education was strongly associated with having higher knowledge scores (p-value = 0.001). Additionally, having attended an educational program on diabetes was moderately associated with higher practice scores (p-value = 0.026). Conclusions Findings of this study highlighted the need for appropriately designed interventions to increase knowledge about T2DM among patients with low educational level. Well-designed educational programs might promote healthy practice among patients with T2DM. Future studies are still needed to assess if such interventions could be effective in improving health outcomes and quality of life of patients with T2DM in Palestine.